Genome-based classification of Streptomyces anatolicus sp. nov., an actinobacterium with antimicrobial and cytotoxic activities, and reclassification of Streptomyces nashvillensis as a later heterotypic synonym of Streptomyces tanashiensis - Ates, Hilal; Saygin, Hayrettin; Cora, Merve; Kilic, Ali Osman; Ay, Hilal (SPRINGER, 2023)
During the course of isolating novel actinobacteria producing bioactive metabolites, strain BG9H(T) was obtained from an arid soil sample in Erzurum, Turkey. Pairwise sequence comparisons for 16S rRNA gene sequences showed the strain was a member of the genus Streptomyces and it shared the highest 16S rRNA gene sequence identity of 99.7% with Streptomyces huasconensis HST28(T). Comparative genome analyses based on digital DNA-DNA hybridization and average nucleotide identity revealed that strain BG9H(T) represents a novel species within the genus Streptomyces. The polyphasic analysis also confirmed that the strain has typical characteristics of the genus Streptomyces. The strain has LL-diaminopimelic acid as diagnostic amino acid, and galactose, mannose and trace amounts of glucose and ribose as whole-cell sugars. Polar lipid profile consisted of diphosphatidylglycerol, phosphatidylethanolamine, phosphatidylinositol, unidentified aminolipids, phospholipids and lipids. Major isoprenoid quinones were MK-9(H-6), MK-9(H-4), and MK-9(H-8). Its genome size is approximately 7.2 Mb with 71.2% G+C content. The methanolic extract of strain BG9H(T) showed antimicrobial and cytotoxic activities. Further genomic analyses of strain BG9H(T) confirmed its high potential to produce novel secondary metabolites. On the basis of phenotypic and phylogenetic analyses, strain BG9H(T) represents a novel species of the genus Streptomyces, for which Streptomyces anatolicus sp. nov. is proposed, and it holds high promise for novel biosynthetic metabolites of value to the biopharmaceutical industry. We also propose Streptomyces nashvillensis as a later heterotypic synonym of Streptomyces tanashiensis as a result obtained through analysis of overall genome relatedness indices.
Keywords: Actinobacteria; Antimicrobial activity; Cytotoxic activity; Genome mining; Phylogenomic; IDENTIFICATION; SEQUENCES; PRODUCER; CLUSTER; GROWTH; Microbiology